UPAYA MENCEGAH TINDAKAN BULLYING ANTAR SISWA MELALUI PENGUATAN BUDAYA SEKOLAH RAMAH ANAK - Yoseptry, Ricky; Meilani, Vivi; Suryani, Yani; Saputra, Doni Ade; Timurita, Novalia Wahyu; Suherman, Suherman (STKIP PGRI Situbondo, 2025)
The phenomenon of violence in schools increases every year. The Indonesian government has issued various policies to prevent violence against children, including violence that occurs in schools. One of them is the Regulation of the Minister of State for Women's Empowerment and Child Protection of the Republic of Indonesia Number 8 of 2014 concerning the child-friendly school policy. This study aims to determine and analyze efforts to prevent bullying between students by strengthening the culture of child-friendly schools. This study uses a qualitative approach with a case study method at Nusa Indah Elementary School, Cipanas District, Cianjur Regency. Data collection techniques include participatory observation, in-depth interviews, and documentation studies of the principal, teachers, students, and parents. The results of the study indicate that planning has not been carried out in a participatory manner and is not supported by written documents specifically for anti-bullying. Organization is not optimal because the Violence Prevention and Handling Team (TPPK) has not been formed. Program implementation focuses more on general character building without specific anti-bullying activities. Evaluation is also not data-based and does not produce concrete follow-up. In conclusion, the child-friendly school culture at Nusa Indah Elementary School has not been implemented effectively in preventing bullying due to the weak school managerial system. Structured planning, involvement of school residents, and continuous data-based evaluation are required.